PERAN PEMERINTAH DAERAH KABUPATEN SOLOK DALAM PENGEMBANGAN PARIWISATA TAHUN 2022 - Rinaldi, Rendy; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the role of the Regional Government of Solok Regency in tourism development, particularly in X Koto Singkarak and Gunung Talang Districts in 2022. These two districts possess significant tourism potential in terms of natural beauty, cultural richness, and local products. However, tourism development in the region still faces challenges such as limited infrastructure, natural disaster risks, low community participation, and weak coordination among stakeholders. The research employs a descriptive qualitative approach using Geoffrey C. Gunn’s theory (1994), which identifies seven strategic roles of government: policy-making, planning, coordination, regulation, stimulation, control, and public ownership. Data were collected through interviews, documentation, and literature review. The results show that the Solok Regency Government has fulfilled several strategic roles, such as formulating Regional Regulation No. 5 of 2020, mid-term tourism planning (RIPPDA), and empowering local communities through training on homestay management and small enterprises. However, low public participation and suboptimal digital promotion remain major obstacles. The study recommends strengthening the government’s role as facilitator and coordinator, improving infrastructure, aligning policies across institutions, and optimizing collaboration with the private sector and local communities. With an inclusive and sustainable strategy, the tourism potential of Solok Regency can be developed to make a significant contribution to community welfare. Keywords: Government Role, Tourism Development, Solok Regency, Gunn’s Theory, X Koto Singkarak, Gunung Talang.